2011
DOI: 10.1007/s00586-011-1837-z
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spine sagittal alignment variations following posterior spinal fusion and instrumentation for adolescent idiopathic scoliosis

Abstract: The aim of this study is to quantify the changes in the sagittal alignment of the cervical spine in patients with adolescent idiopathic scoliosis following posterior spinal fusion. Patients eligible for study inclusion included those with a diagnosis of mainly thoracic adolescent idiopathic scoliosis treated by means of posterior multisegmented hook and screw instrumentation. Pre and post-operative anterior-posterior and lateral radiographs of the entire spine were reviewed to assess the changes of cervical sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 31 publications
4
52
0
1
Order By: Relevance
“…Hilibrand et al [2] reported a result of 6°of kyphosis for cervical spine and a phenomenon that a hypo-kyphotic thoracic spine accompanies a kyphotic cervical spine before operation. Canavese et al [3] found that 34.4 % of patients with adolescent idiopathic scoliosis (AIS) had an average of 11°c ervical kyphosis, with their thoracic kyphosis \17°.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hilibrand et al [2] reported a result of 6°of kyphosis for cervical spine and a phenomenon that a hypo-kyphotic thoracic spine accompanies a kyphotic cervical spine before operation. Canavese et al [3] found that 34.4 % of patients with adolescent idiopathic scoliosis (AIS) had an average of 11°c ervical kyphosis, with their thoracic kyphosis \17°.…”
Section: Introductionmentioning
confidence: 99%
“…The previous researches provide us the fact that a hypokyphotic thoracic spine coexists with a kyphosis in cervical spine in idiopathic scoliosis [2,3]. However, overemphasis on the modification of isolated angles could render us neglect of their further association with the global spine alignment.…”
Section: Introductionmentioning
confidence: 99%
“…13,19 Studies of the treatment of idiopathic scoliosis in adolescents have shown that loss of thoracic kyphosis as a result of surgical coronal plane correction of the scoliosis is associated with a postoperative increase in cervical kyphosis. 1,6,7 Studies of sagittal alignment include either occipitocervical or thoracolumbopelvic regions, but limited data regarding the connection of these regions are available. 11 The SVA is usually measured by using C-7 or C-2 as bony landmarks (C-7 SVA or C-2 SVA), so it is likely that changes in cervical alignment might influence the overall balance, necessitating further studies of the relationship between the occipitocervical spine and the thoracolumbopelvic region.…”
mentioning
confidence: 99%
“…On the other hand, several authors have reported a worsening of the cervical sagittal alignment following correction of the thoracolumbar curves, demonstrating the importance of the relationship between these curves in the postoperative period. 5,16 These studies have limitations: the number of cases in our study, while not insufficient, is a factor that limits a more comprehensive evaluation. Secondly, the variety of curves operated on, that is, the heterogeneity of the curves in the same sample is a limitation.…”
Section: Contributions Of the Authorsmentioning
confidence: 89%
“…Canavese et al 5 showed that scoliotic thoracic hypokyphosis is associated with lordosis rectification or even cervical kyphosis, with evidence of degenerative cervical changes following surgical treatment. These changes were also found following surgical treatment, with an incidence of late postoperative cervical pain of between 17 and 57%.…”
Section: Introductionmentioning
confidence: 99%